Towards low-emission food systems in Guinea: A country profile - Pingault, N.; Martius, C. (CIFOR-ICRAF, 2026)
Food systems—spanning agriculture, land use and land-use change and forestry (LULUCF), energy, industrial processes and product use (IPPU), and waste—account for about one third of global anthropogenic greenhouse gas emissions, yet they remain an often underreported component of the climate challenge. This country profile on Guinea is part of a broader series that applies a food-system lens to national emissions by combining international datasets with official country reporting. It provides an integrated overview of land use, forests and agriculture, food security and diets, and food system emissions in Guinea, where agriculture, forestry, fisheries, and food processing and distribution are central to livelihoods, and where waste management is an increasingly important urban activity. Drawing on FAOSTAT data and Guinea’s 2024 Biennial Update Report, the profile compares international and national estimates to identify the main sources of food system emissions and areas of convergence between datasets. The analysis shows that Guinea’s food system emissions are dominated by farm-gate sources—particularly livestock methane, rice cultivation, and manure-related emissions—followed by land-use change driven largely by shifting cultivation and agricultural expansion, while emissions beyond the farm gate remain smaller but are increasing in urban areas due to waste disposal and energy use. The profile situates these emissions within a context of rapid population growth, persistent poverty, strong reliance on smallholder rainfed agriculture, and diets heavily dependent on rice and starchy staples, with low overall protein intake. It identifies a set of no-regret mitigation priorities that combine emissions reduction with food security and development objectives, including improved livestock productivity, methane-smart rice cultivation and loss reduction, forest regeneration and frontier control, and urban waste management solutions. By making food system emissions more visible and policy-relevant, this publication aims to support policymakers, researchers, and development partners in identifying climate actions aligned with Guinea’s development priorities and future climate commitments.